PENGARUH PENGGUNAAN FUNGISIDA SINTETIS DAN Trichoderma sp. SECARA TUNGGAL ATAU GABUNGAN TERHADAP PENYAKIT HAWAR PELEPAH DAUN PADI EFFECT OF SYNTHETIC FUNGICIDAL APPLICATION ALONE OR MIXED WITH Trichoderma sp. ON SHEAT BLIGHT OF RICE - Susilo, Pambudi; Soesanto, Loekas; Wachjadi, Muljo (Pembangunan Pedesaan, 2005)
This research aimed at knowing the application effect of synthetic fungicide tebuconazole 25% alone or mixed with Trichoderma sp. on sheath blight disease and rice yield. The research was carried out at the Plant Disease Laboratory and the experimental field, the Faculty of Agriculture, the University of Jenderal Soedirman. Split Plot Design was used with Trichoderma sp. as main factor consisted of without and with antagonistic Trichoderma sp. applied on rice at 15, 30, and 45 and 55 days after transplanting (dat), and concentration of tebuconazole -1 25% as sub-plot consisted of 0, 0.5, 1.0, 1.5, and 2.0 g l . The combination was repeated three times. Variables observed were incubation period, disease intensity, phytoxicity, effectiveness of the fungicide, number of young crops, and dry weight of harvested unhulled rice. Data were analyzed with F test and continued with LSD at level of 5%. Result of the research pointed out that average of incubation period was in the range of 20-30 dat. The application of Trichoderma sp. at 15 and 30 dat could suppress the disease development around 17.01 and 10.73%, respectively. The fungicide tebuconazole 25% applied at all concentration could suppress the disease development around 20.01-23.34%; did not cause toxicity to the crops, less effectiveness, and could not increase the numbers of young crops and rice yield. Trichoderma sp. applied at 15, 30, 45, and 55 dat could not increase the numbers of young crops and rice yield. The combination did not affect the disease intensity, numbers of young crops, and rice yield.